Exploring Health Consumer Behavior During Covid-19: A Bibliometric Analysis - Nanang Suryadi; Kardina Yudha Parwati; Abdurrahman Hakim; RR Ayu Firdausiah; Muhammad Fajrul Islam Fasieh (Asia Pacific Journal of Management and Education (APJME), 2023)
For more than three decades, marketers' primary focus has been directed toward consumer behavior patterns. During COVID-19, marketing science experts have paid particular attention to the behavioral change in consumer buying-related health areas. By highlighting the research themes using bibliometric analysis and providing an agenda for future research, this study aims to analyze the trends in consumer behavior in the health aspect. The bibliographic information for 34 papers was gathered from Scopus, one of the most well-known academic indexing databases. The study used open-source software tools like VOS Viewer and NVIVO to conduct various bibliometric analyses. Based on our bibliometric analysis, this study was related to a number of themes of consumer behavior of health aspects, including consumer lifestyle, consumer buying behavior, consumer health awareness, health behavior, perceived health benefit, and consumer health risk. The results from co-authorship analysis indicate that there is no particular connection between the topic of consumer behavior on the health aspect that different authors explore since each research focuses on a specific topic. For research academics in the academic community, the analysis of scientific research will serve as a reference manual for understanding the theoretical underpinnings of research on consumer behavior, identifying knowledge gaps, and suggesting future research direction.